General Versus Spinal Anesthesia in Percutaneous Nephrolithotomy - Mehrabi, Sadrollah; Mousavi Zadeh, Ali; Akbartabar Toori, Mehdi; Mehrabi, Farhad (Urology Journal, 2013)
PURPOSE: To compare efficacy and complications of spinal anesthesia versus general anesthesia in percutaneous nephrolithotomy (PCNL). MATERIALS AND METHODS: In a prospective randomized study, 110 patients were randomly assigned into two groups for PCNL; group 1 (n = 52) underwent general anesthesia and group 2 (n = 58) received spinal anesthesia. In group 1, PCNL was performed using standard technique under general anesthesia. In group 2, spinal anesthesia was done by injecting bupivacaine and fentanyl in spinal space L4 in sitting position. Thereafter, a urethral catheter was placed in lithotomy position, head of the bed was tilted down for 5 to 10 minutes, and the level of anesthesia was checked. Then, PCNL was done by standard technique. Complications were recorded and analyzed by SPSS software using Chi-Square and Student’s t tests. RESULTS: Mean stone size in groups 1 and 2 was 34.2 ± 9.8 mm and 31.3 ± 7.9 mm, respectively. Intra-operative hypotension and postoperative headache and low back pain were more in spinal group than the general group with a significant difference (P < .05). No neurologic complication was observed in both groups. Need to narcotic medications on the day of operation in groups 1 and 2 was 12.4 ± 3.1 mg and 7.8 ± 2.3 mg of morphine sulphate, respectively (P = .03). The cost of anesthetic drugs was 23 ± 3.7 US and 4.5 ± 1.3 US in groups 1 and 2, respectively (P = .001). CONCLUSION: Spinal anesthesia with combined bupivacaine and fentanyl is a safe, effective, and cost-effective method for performing PCNL in adult patients.